Identification of Nursing Problems in Hospitalized Patients with Diabetes Mellitus - Wikan Purwihantoro Sudarmaji; Nursalam Nursalam; Sartika Wulandari (Universitas Airlangga, 2020)
Introduction: One of the duties of nurses when managing patients with diabetes mellitus is establishing a nursing diagnosis. This study aimed to identify the nursing problems that arise in hospitalized patients with diabetes mellitus. Methods:A descriptive analytical study involving 100 medical records of inpatients with diabetes mellitus from June, July and August 2019 was conducted. The data collection was done through an observation sheet according to the Indonesian Nursing Diagnosis Standards (SDKI). Results: There were 30 types of nursing problems identified with the total number of nursing problems found being 332. The most frequent nursing problems were D.0142 Risiko Infeksi (Risk of Infection) 30.12%, D.0027 Ketidakstabilan Kadar Glukosa Darah (Instability of Blood Glucose Levels) 14.16%, D.0011 Risiko Penurunan Curah Jantung (Risk of Decreased Cardiac Output) 12.65%, D.0017 Risiko Perfusi Serebral Tidak Efektif (Risk of Cerebral Perfusion Not Effective) 8.73%, D.0037 and Risiko Ketidakseimbangan Elektrolit (Risk of Electrolyte Imbalance) 4.52%. Conclussion: This research found there to be 30 variations of nursing problems among the hospitalized patients with diabetes mellitus with the most frequent nursing problems in the physiological category and nutrition and fluid sub-categories.